2022
DOI: 10.1002/bse.3270
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship between international trade and environmental performance: Theoretical approaches and indicators for sustainable development

Abstract: In recent years, a great deal of research has analyzed the impact of trade openness on the environment, with the aim of determining whether internationalization contributes to the improvement of environmental performance (EP) or, on the contrary, hinders the achievement of sustainable development. The objective of the present work is to conduct a systematic literature review on the interrelationship between international trade and EP at the micro‐ and macroeconomic levels, analyzing the existent theoretical ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 142 publications
0
6
0
Order By: Relevance
“…Xu et al [18] show that international trade positively affects the global process of achieving the nine environment-related Sustainable Development Goals (SDGs). Moreover, in addition to the studies that concluded a positive effect of international trade on environmental quality, according to a review study by Sorroche-del-Rey et al [19], 20.68% of the studies showed that international trade has a negative effect on environmental quality, and this negative effect is due to the negative impact on the environment of developing countries as a result of the use of developing countries as "pollution havens" by developed countries. Wang et al [20] investigate the impacts of structural changes in global trade on 13 SDGs, and the results showed that structural changes in trade have the greatest impacts on environmental indicators.…”
Section: Sustainable Tradementioning
confidence: 99%
“…Xu et al [18] show that international trade positively affects the global process of achieving the nine environment-related Sustainable Development Goals (SDGs). Moreover, in addition to the studies that concluded a positive effect of international trade on environmental quality, according to a review study by Sorroche-del-Rey et al [19], 20.68% of the studies showed that international trade has a negative effect on environmental quality, and this negative effect is due to the negative impact on the environment of developing countries as a result of the use of developing countries as "pollution havens" by developed countries. Wang et al [20] investigate the impacts of structural changes in global trade on 13 SDGs, and the results showed that structural changes in trade have the greatest impacts on environmental indicators.…”
Section: Sustainable Tradementioning
confidence: 99%
“…Besides, the CEP is also closely correlated with corporate ownership. In response to the “pollution halo” hypothesis (Birdsall & Wheeler, 1993; Grossman & Krueger, 1991; Sorroche‐del‐Rey et al, 2022; Wang et al, 2021), more studies have found that foreign‐owned enterprises (associated with foreign direct investment) are more likely to adopt environmentally friendly production and management practices than domestic‐owned enterprises in developing countries (Li et al, 2018; Wang & Jin, 2007). The government and society also impose greater environmental requirements and social responsibility on foreign‐owned enterprises comparing to domestic‐owned enterprises.…”
Section: Theoretical Basis and Hypothesis Formulationmentioning
confidence: 99%
“…At a microeconomic level, only 25% of theses works examine whether EI helps companies increase EX. Nevertheless, most of them (75%) analyze the influence of EX on EI, confirming mostly a positive effect (Sorroche-del-Rey et al, 2022). Moreover, it can be observed that most of the analyses have focused on the industrial sector, and the evidence in the agro-food sector is very scarce.…”
Section: Introductionmentioning
confidence: 99%